Ceramic-Based Bone Grafts as a Bone Grafts Extender for Lumbar Spine Arthrodesis: A Systematic Review. (August 2014) - Nickoli, Michael S.; Hsu, Wellington K.
Study Design: Systematic review. Objective: Ceramic-based bone grafts have been widely utilized to reduce the need for iliac crest bone grafting given the complications associated with the harvest of iliac crest autograft. As a family, ceramics vary widely based on differences in composition, manufacturing, porosity, and structure, which may ultimately affect their efficacy. This article reviews the current data of ceramics used in different environments in the lumbar spine to achieve arthrodesis. Methods: Medline, EMBASE, and Cochrane Central Register of Controlled Trials were searched for publications from 1980 to 2013 involving ceramic-based bone grafts in the lumbar spine. Variables such as age of patients, volume of ceramic, procedure, time to evaluation, method of evaluation, specific composition of ceramic, adjuncts used with ceramic products, type of fusion, and fusion rate were compared using a multivariate logistic regression model. Results: Thirty studies with 1, 332 patients met the final inclusion criteria. The overall fusion rate for all ceramic products as a bone graft extender in the lumbar spine was 86.4%. Age, gender, method of evaluation (plain radiographs, computed tomography, or combination), or specific ceramic product did not significantly affect fusion rate. Ceramics used in combination with local autograft resulted in significantly higher fusion rates compared with all other adjuncts, and bone marrow aspirate and platelet concentrates resulted in significantly lower fusion rates. Conclusions: Ceramic-based bone grafts represent a promising bone graft extender in lumbar spine fusion when an osteoinductive stimulus, such as local bone graft is available.